2022
DOI: 10.20473/jiet.v7i2.40679
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Financial Literacy and Financial Behavior on Investment Intention

Abstract: The low level of financial literacy, especially Islamic financial literacy which can affect individual readiness to plan finances and accept risks in relation to financial investments. This research aims to determine the effect of Islamic financial literacy and financial behavior on investment intentions.. The research used in this research is quantitative research with the questionnaire method on google form to respondents as well as using secondary data derived from literature and the results of previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 6 publications
3
9
1
1
Order By: Relevance
“…However, upon further exploration, we identify crucial differences in the direct impact of these two variables on investment decisions. Our findings indicate that Sharia financial literacy has a weaker direct influence on investment decisions compared to previous research, which suggested a stronger direct impact (Roemanasari et al, 2022). This could be attributed to other factors influencing investment decisionmaking, such as investment risk or individual preferences.…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…However, upon further exploration, we identify crucial differences in the direct impact of these two variables on investment decisions. Our findings indicate that Sharia financial literacy has a weaker direct influence on investment decisions compared to previous research, which suggested a stronger direct impact (Roemanasari et al, 2022). This could be attributed to other factors influencing investment decisionmaking, such as investment risk or individual preferences.…”
Section: Resultscontrasting
confidence: 82%
“…In this research, we successfully identify and analyze the complex relationship among Sharia financial literacy, financial attitudes, financial satisfaction, and investment decisions. Our primary findings align with the theoretical framework, demonstrating that sound knowledge of Islamic finance and a positive attitude towards finance can enhance an individual's satisfaction with their financial situation (Roemanasari et al, 2022). However, upon further exploration, we identify crucial differences in the direct impact of these two variables on investment decisions.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…As research (Roemanasari et al, 2022), (Arifin & Rizaldy, 2022) whose results show that Islamic financial literacy affects investment intention. The intention to invest here can be interpreted as a form of Islamic financial inclusion.…”
Section: Discussionmentioning
confidence: 89%
“…Financial literacy is the ability of individuals to utilize the knowledge, beliefs, and skills of consumers and the wider community to better manage financial resources for future prosperity. Meanwhile, Islamic financial literacy is the ability to apply financial knowledge, skills, and attitudes to manage financial resources in accordance with sharia principles (Roemanasari et al, 2022).…”
Section: Sharia Financial Literacymentioning
confidence: 99%